Association between uric acid lowering and renal function progression: a longitudinal study - Liu,Liyi; You,Lili; Sun,Kan; Li,Feng; Qi,Yiqin; Chen,Chaogang; Wang,Chuan; Lao,Guojuan; Xue,Shengneng; Tang,Juying; Li,Na; Feng,Wanting; et al. (PeerJ, 2021)
Background This study aimed to explore the association between uric acid lowering and renal function. Materials and Methods We conducted a population-based cohort study with 1,534 subjects for 4 years from 2012 to 2016. The population was divided into four groups according to the interquartile range of changes in serum uric acid with quartile 1 representing lower quarter. Renal function decline was defined as eGFR decreased more than 10% from baseline in 2016. Renal function improvement was defined as eGFR increased more than 10% from baseline in 2016. Cox regression analysis was used to calculate the hazard ratio (HR) and 95% confidence interval (CI). Results In the adjusted Cox regression models, compared to quartile 4, quartile 1 (HR = 0.64, 95% CI [0.49–0.85]), quartile 2 (HR = 0.65, 95% CI [0.50–0.84]) and quartile 3 (HR = 0.75, 95% CI [0.58–0.96]) have reduced risk of renal function decline. An increasing hazard ratio of renal function improvement was shown in quartile 1 (HR = 2.27, 95% CI [1.45–3.57]) and quartile 2 (HR = 1.78, 95% CI [1.17–2.69]) compared with quartile 4. Conclusions Uric acid lowering is associated with changes in renal function. The management of serum uric acid should receive attention in clinical practice and is supposed to be part of the treatment of chronic kidney disease.
Keywords: Uric acid lowering; Renal function; Chronic kidney disease; Population-based study